Quail Production Systems, Prospects and Constraints in Ghana - Akarikiya, Samuel Azebadumah; Dei, Herbert Kwabla; Mohammed, Alhassan (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2022)
ABSTRACT This study was undertaken to assess the production systems, prospects and challenges of quail farming in three (3) ecological zones (Rainforest, Transitional and Guinea Savannah) in Ghana. Sixty (60) quail farmers were purposefully sampled for the study using the snowball sampling technique. Data were gathered through interviews with the aid of structured questionnaire and analysed using SPSS 22.0. The results showed that more males (86.7%) than females (13.3%) were involved in quail farming in Ghana with majority (73.3%) of farmers having less than five years of experience in the business. About 50% of quail farmers had their flock sizes ranging from 501 to 2000 birds. Three (3) major breeds of quails (Japanese, American and Jumbo Giant quails) are reared in Ghana but the most common breed is the Japanese quail due to its prolificacy and ability to tolerate the intensive colony battery cage management system for commercial egg production. Quail production was more prevalent in the ecological zones in Southern Ghana than in the Northern Guinea Savannah zone.